Penerapan Model Pembelajaran Think Talk Write untuk Meningkatkan Hasil Belajar Siswa pada Tema Daerah Tempat Tinggalku di Kelas IV SD PAB 23 Patumbak - Khairani, May; Nasution, Ahmad Landong (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This study aims to improve student learning outcomes in class IV SD PAB 23 with the theme "Where I Live" by applying the Think Talk Write Learning Model. This research was conducted in class IV SD PAB 23 Patumbak. This research is a class action research (Classroom Action Research). The subjects in this study were 25 grade IV SD PAB 23 Patumbak students, 13 male students and 12 female students. Instruments and data collection techniques used in this study are observation and tests. From the observation results, it is known that the overall teacher activity in cycle I with the application of the Think Talk Write Learning Model is 72.7% in the sufficient category. The results of observations of student activity as a whole in cycle I, namely 70% in the sufficient category with the percentage of completeness of student learning outcomes in cycle I was 70.8% in the sufficient category. Overall teacher activity in cycle II was 81.81% in the good category. Overall student activity in cycle II was 82.5% in the good category with the percentage of completeness of student learning outcomes in cycle II was 80.32% in the good category. Overall teacher activity in cycle III was 93.18% in the very good category. Overall student activity in cycle III, which is 92.5% in the very good category with the percentage value of the completeness of student learning outcomes in cycle III is 92.36% in the Very Good category. Thus it can be concluded that the Application of the Think Talk Write Learning Model can improve results student learning on the theme The Area Where I Live, class IV SD PAB 23 Patumbak..